Factors Affecting the Development of Handicrafts Products at Donkeo Village, Luang Prabang City: https://doi.org/10.69692/SUJMRD100485 - BOUNATHONE, Thiphasone; HOONGSENGPHA, Soudthida; INDAVONG, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research were to study the overall situation of producers in Donkeo village, and analyze factors affecting the handicraft products development of Donkeo village, Luang Prabang City. Quantitative methods were used, 40 questionnaires were delivered to the weavers, and descriptive statistics and inferential statistics were used as analyses. The results showed that environmental factors overall using SWOT analysis were at a high level ( = 3.81). The five forces analysis showed overall was at a high level ( = 3.80). The degree of factors affecting the level of handicraft product development overall was high level ( = 4.00). The PEST analysis showed that overall was at a high level ( = 3.86). The factors affecting the level of handicraft product development overall were high level ( = 3.78). Environmental factors were affected by the results of the handicraft product development of Donkeo village in Luang Prabang City consisting of opportunity X3 (b=0.209). The competitiveness forces factors were affected by the results of the handicraft product development of Donkeo village in Luang Prabang City consisting of the threat of substitution (b=0.259), and competitive rivalry (b=0.259). Internal forces factors affected the results of the handicraft product development of Donkeo village in Luang Prabang city consisting of characteristics (b=0.204), and the external factors affected the results of the handicraft product development of Donkeo village in Luang Prabang city consists of economic (b=0.329).